Diabetes Management in Working Age Group: The Challenging for Nurse Practitioners - Senachai, Naovarat; Mangklakeeree, Nutcharat; Panput, Anantasak (Journal of The Royal Thai Army Nurses, 2021)
Diabetes mellitus (DM) is a chronic and complex disease that impacts on the lives and well-being of individual life, family, community, social and countries, particular increasing number of diabetes people in working age group. The challenging for people with diabetes that they need long-term care through multiple tasks that requires change in their lifestyle. This is quite difficult for adult population with diabetes, who are responsible their role and responsibility both of themselves and their family, they also need to learn skills and tasks to manage the disease for preventing or delaying complications by controlling blood glucose. This article focused on the challenge for nurse practitioners on diabetes self-management education and support (DSMES) to enhance and maintain self-care behaviors in working age group, based on the American Association of Diabetes Educations (AADE), AADE7 self-care behaviors and expanded chronic care model (ECCM).